2015
DOI: 10.1596/1813-9450-7161
|View full text |Cite
|
Sign up to set email alerts
|

Survival is for the Fittest: Export Survival Patterns in Georgia

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
1
3
2
Order By: Relevance
“…From Figure 3 it can be deduced that the survival rate is higher for firms with a holding company that is resident outside South Africa: the survival rate is over 95 per cent by year seven of the study in this group, compared with below 90 per cent for locally owned firms. This is in line with Martuscelli and Varela (2015), who found that foreign-owned firms' survival rate was on average 2.8 per cent higher. However, the trend is reversed by the end of the study period, as local firms' survival rate is about 87 per cent, but for foreign-owned firms it is around 85 per cent.…”
Section: Firm Survival In the Export Marketsupporting
confidence: 90%
See 2 more Smart Citations
“…From Figure 3 it can be deduced that the survival rate is higher for firms with a holding company that is resident outside South Africa: the survival rate is over 95 per cent by year seven of the study in this group, compared with below 90 per cent for locally owned firms. This is in line with Martuscelli and Varela (2015), who found that foreign-owned firms' survival rate was on average 2.8 per cent higher. However, the trend is reversed by the end of the study period, as local firms' survival rate is about 87 per cent, but for foreign-owned firms it is around 85 per cent.…”
Section: Firm Survival In the Export Marketsupporting
confidence: 90%
“…Many markets have been shaken since the global financial crisis of 2007, with a great swing in fortunes over the years; therefore, diversifying markets can be a significant survival strategy for firms, as the results here suggest. However, these results contradict finings by Martuscelli and Varela (2015), who argue that product diversification is more beneficial that market diversification.…”
Section: Firm Survival In the Export Marketcontrasting
confidence: 65%
See 1 more Smart Citation
“…Several papers have since followed this approach, including most recently Martuscelli and Varela (2015). This paper focuses on a random effects discrete-time logit model with log of time, 12 while also presenting Cox and logit model regression results for comparison.…”
Section: (D) Estimation Strategymentioning
confidence: 99%
“…Reverting to another flipside of this study is the methodological debate that has seen contemporary studies prefer discrete-time models over continuous-time models. The main nuance rose from the results of Hess and Person (2012) Martuscelli et al (2015) in their justification for using their discrete-time model on Georgian firm-level data for 2006 to 2012. 37 It is what was published as Hess and Persson (2012) found that parity on export survival was likely to be maintained when one country exported many products to many markets 38 , an export relationship started small and grew over time, common language, colonial history, distance, EU membership, prior experience, depreciated exporter exchange rates, differentiated products and high importer GDP.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%